Islamic Micro Finance Melati: Sebuah Upaya Penguatan Permodalan bagi Pedagang Pasar Tradisional - Sabirin Sabirin; Dini Ayuning Sukimin (Economica: Jurnal Ekonomi Islam, 2017)
The purpose of this research is to examines Islamic Micro Finance Melati (Melawan Rentenir) in helping traders in traditional markets to avoid the practice of loan sharks. This article uses descriptive explorative approach by analyzing the right strategy in the management of islamic micro finance institution targeting especially for traders in traditional market in Indonesia. From this study obtained the following conclusions. First, the design of Islamic Micro Finance Melati in order to create an easy Islamic microfinance institution in providing capital financing is very suitable in overcoming the practice of loan shark. Second, working capital is channeled using a system of cooperation whereby the trader is obliged to return the principal and profit share of the profit. Third, the organizational structure and management patterns that are not complicated will make Islamic Micro Finance Melati is easy to realize. Fourth, the existence of Islamic Micro Finance Melati can be an example for other Islamic microfinance institutions in managing management strategy so that sharia microfinance institution can be the main choice for micro business actors.Tujuan penelitian ini untuk mengkaji Islamic Micro Finance Melati (Melawan Rentenir) dalam membantu pedagang di pasar tradisional dari praktik rentenir. Penelitian ini menggunakan pendekatan eksploratif deskriptif dengan menganalisis strategi yang tepat dalam pengelolaan lembaga keuangan mikro syariah yang menyasar para pedagang di pasar tradisional di Indonesia.Dari penelitian ini diperoleh kesimpulan: Pertama, desain Islamic Micro Finance Melati dalam rangka menciptakan lembaga keuangan mikro syariah yang mudah dalam memberikan pembiayaan permodalan sangat cocok dalam mengatasi praktik rentenir. Kedua, modal kerja yang disalurkan menggunakan sistem kerjasama dimana pedagang wajib mengembalian pokok dan bagi hasil dari keuntungan. Ketiga, struktur organisasi dan pola pengelolaan yang tidak rumit akan membuat Islamic Micro Finance Melati ini mudah untuk direalisasikan. Keempat, keberadaan Islamic Micro Finance Melati dapat menjadi contoh bagi lembaga keuangan mikro syariah lainnya dalam pengelolaan strategi pengelolaan sehingga lembaga keuangan mikro syariah dapat menjadi pilihan utama bagi pelaku usaha mikro.